GIVING COLOSTRUM TO BABIES AT THE POSYANDU IN THE WORK AREA PUSKESMAS TANJUNGBATU, GADING SARI VILLAGE - Meirina Daulay; Wennas Wennas (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : Based on the results of love, the Indonesian Demographic and Health Survey (IDHS) in 2008 explained that in 2002–2003 exclusive breastfeeding for babies aged 2 months was only 64%. This percentage has decreased markedly to 46% in infants aged 2–3 months and 14% in infants aged 4–5 months. Other conditions of concern are 13% and infants aged 2 months have been given formula milk and 15% have been given additional food. Breastfeeding in the first hour will prevent the mother from the dangers of breast engorgement and blocked milk ducts. The research objective was to determine the provision of colostrum to infants at Posyandu. Method : This research method is descriptive. The research site will be conducted in the Posyandu in the working area of the Tanjungbatu Community Health Center, Gading Sari Village. The population in this study were all mothers of infants who visited or conducted examinations at the Posyandu in the working area of the Tanjungbatu Public Health Center, Gading Sari Village. The population in this study had an average number of visits per month, namely 65 people. Sampling in this study using total sampling, which then sampling is the mother of infants who meet the criteria. Univariate analysis is used to determine the frequency distribution of the variables that have been determined in the study. Result : From the results of the research conducted, it can be seen that as many as 37 respondents did not give colostrum to babies (56.9%), while as many as 28 respondents gave colostrum to babies (43.1%).